Problematika Maharoh Qiro’ah Dalam Pembelajaran Bahasa Arab Di MTs Fatahillah Probolinggo - Rohmah, Ainur; Zainullah, Ahmad (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
Reading is one of the language skills that must be achieved by students. The success of students in participating in the teaching and learning process at school is determined by their mastery of reading skills. Students who cannot read will have difficulty participating in learning activities for all subjects including Arabic language lessons. This study uses a qualitative method. The data collected in this research was by observation (seeing the conditions at school directly), as well as by interviewing teachers who taught Arabic subjects to find out the problems that occurred among class VII students at MTs Fatahillah. The results of these findings are: when pronouncing the reading is not correct (not in accordance with tajwid), there are still those who read not in accordance with the makharijul letters, reading is still spliced ??(there are no semicolons), reading is still like reading the Al-Qur'an , and also do not understand the content in Arabic reading. Apart from that, the background conditions of class VII MTs Fatahillah students vary in their reading abilities. For students who have basic skills, reading ability will make learning easier, whereas those without basic skills will have difficulty following the material. Solutions that researchers can offer to solve the problems that occur include: Drill method (procedure repetition practice technique), singing/songs, and peer tutoring (using peers as additional learning resources).